Subclinical Changes in Type 2 Diabetes Patients with Heart Failure Stage A and B Treated with Oral Semaglutide - Larissa Dăniluc; Adina Braha; Oana Elena Sandu; Carina Bogdan; Loredana Suhov; Lina Haj Ali; Alexandra-Iulia Lazăr-Höcher; Alexandra Sima; Adrian Apostol; Mihaela Viviana Ivan (Medicina)
Background and Objectives: Heart failure (HF) among patients with type 2 diabetes (T2DM) is linked to significant morbidity and mortality, despite the increased availability of new drug therapy. This study aims to investigate subclinical changes in patients with HF stage A (at risk for HF) and B (Pre-HF) and T2DM treated with oral semaglutide. Materials and Methods: In a prospective, observational, single-center study, 50 T2DM patients were assessed at baseline and one-year follow-up for changes in spectral Doppler, tissue Doppler, and speckle-tracking (2DST) and metabolic parameters. Results: Correlation and regression analyses identified predictors of Δ GLS. In correlation analysis, Δ GLS showed a negative correlation with Δ VAI (rho = −0.3, p = 0.02), Δ LAP (rho = −0.3, p = 0.04), Δ FPG (rho = −0.3, p = 0.009), Δ TG (rho = −0.4, p = 0.004), and Δ TyG (rho = −0.3, p = 0.02). In linear stepwise regression analysis, the most accurate model, with a p-value < 0.001, was M3, explaining 70% of the variance in Δ GLS (adjusted R2 = 0.7); this model included Δ FPG (beta −0.4, p = 0.001), Δ CRR (beta −1.3, p < 0.001), and Δ LDLc (beta 0.6, p = 0.01). Conclusions: These findings show that improved subclinical left ventricular systolic dysfunction is associated with improved glycemic control, visceral adiposity, and reduced insulin resistance, respectively, with improved lipid profiling.